Identification of Process Skills and Learning Results Through the Treffinger Model - Lasaiba, Mohammad Amin; Arfa, Arman Man (Universitas Pahlawan Tuanku Tambusai, 2023)
The Treffinger model is a learning approach that emphasizes developing students' skills and encouraging learning. This study aimed to analyze the effect of using the Treffinger learning model on process skills and learning outcomes of geography. This research was conducted by dividing students into two groups, namely the experimental and control groups. The research was conducted at MAN 2 Ambon and involved randomly selected class VIII students from September to November. The data analysis technique used was multivariate (MANOVA) with the help of SPSS 26.0 for windows. Based on the research results, the normality test, homogeneity test, and multicollinearity show that the data is normally distributed, homogeneous, and collinear.Furthermore, based on hypothesis testing, there are significant differences in process skills and learning outcomes between students who study with the Treffinger learning model and students who learn with conventional learning models. The Treffinger learning model shows a better effect with a calculated F value = 12.85, and the significance level for Pillai's Trace, Wilks' Lambda, Hotelling's, and Roy's Largest Root is less than 0.05. Whereas for the test between subjects, the value of F = 0.116 was obtained with a significance of less than 0.05. Thus, the Treffinger Model is an effective learning model for developing students' creative and innovative thinking skills in improving geography learning outcomes.